Scientific computing with Python 3 : an example-rich, comprehensive guide for all of your Python computational needs /: an example-rich, comprehensive guide for all of your Python computational needs. (2016) - Führer, Claus; Solem, Jan Erik; Verdier, Olivier
No abstract available